PENGARUH REPUTASI MEREK DAN KUALITAS PRODUK TERHADAP LOYALITAS KONSUMEN DAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING PADA PASTA GIGI PEPSODENT DI DESA WONOREJO KECAMATAN SINGOSARI KABUPATEN MALANG (Studi Kasus Pada Konsumen Pasta Gigi Pepsodent Di Desa Wonorejo Kecamatan Singosari Kabupaten Malang) - Nur Laili Khoirunnida; N. Rachma; M. Hufron (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACT               This study is to influence brand reputation and product quality on consumer loyalty and customer satisfaction as an intervening variable in Pepsodent Toothpaste in Wonorejo Village, Singosari District, Malang Regency. The population of this study was consumers of pepsodent toothpaste in Wonorejo village, Singosari district. Samples were taken using the Slovin formula so that 90 respondents were eligibleas samples. This study uses primary data and path analysis methods.               The results of this study indicate that the Brand Reputation and Product Quality variables directly influence significantly the value of Consumer Satisfaction. Brand Reputation Variables have no direct significant effect on consumer loyalty while product quality has a direct and significant effect on consumer loyalty. The variable customer satisfaction has a significant direct effect on consumer loyalty. Variables of brand reputation and product quality indirectly influence consumer loyalty with customer satisfaction as an intervening variable. Keywords: Brand Reputation, Product Quality, Consumer Loyalty, Customer Satisfaction as Iintervening variables.